Inter-organizational business process verification in public administration. Issue 5 (7th September 2015) - Corradini, Flavio; Polini, Andrea; Re, Barbara
Abstract : Purpose: – Public services can be modelled, analysed and implemented using notations and tools for the business process (BP) abstraction. Applying such an explicit approach public administrations (PAs) can better react to the undergoing transformation in service provisioning and they can continuously improve service quality in order to satisfy citizens and business requests, while coping with decreasing budgets. The purpose of this paper is to discuss these issues. Design/methodology/approach: – The proposed approach relies on using formal methods, in particular unfolding to analyse the correctness of BP. The paper also compares and selects mapping rules from semi-formal to formal modelling languages; these techniques are presented in the context of the BP Modelling Languages and Petri Net (PN). Findings: – Main aim of this paper is to raise the need for formal verification of BP governing the interactions among PAs, which more and more need to be supported by ICT mechanisms, and then are not so much tolerant to errors and imperfections in the process specification. The paper illustrates the main motivations of such a work and it introduces a verification technique of a BP using a mapping of a high-level notation (such as BPMN 2.0) to a formal notation (such as PNs) for which formal analysis techniques can be adopted. In particular the verification step is implemented using an unfolding-based technique. Originality/value: – The paper answers a call for further development of the body of knowledge on effective analysis of BPs, a rapidly emerging field of interest for large and ultra large scenarios, where a clear gap in literature exists. Than the paper shows that formal techniques are mature enough to be applied on real scenarios.